A Biographical Novel of the Spanish Civil War: Lydie Salvayre's Pas pleurer (2014) - Gaudet, Jeannette (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2020)
This article focuses on the biographical novel, Pas pleurer (2014) and the author Lydie Salvayre’s development of two diametrically opposed experiences of the Spanish civil war. Pas pleurer deploys the author’s parallel engagement with Montse, Salvayre’s mother, and with Georges Bernanos through a reading and commentary of the polemical essay, Les Grands Cimetières sous la lune. Biographical material provides the ground for intersecting narratives: on the one hand, the Bernanos intertext with its keen analysis of the complicity of secular and religious institutions to maintain control of Spain through terrorism and violence reverberates throughout and finds its echo in the tragic story of Montse’s older brother José. Set against this is the adolescent Montse’s encounter with the dramatic social revolution underway in the Catalan city and her life-altering experience of passionate love, the memory of which remains intact and luminous despite age and disease. Examining both n arratives highlights the act of resistance at the heart of the novel and captured by its title.